Myelopathy associated with SARS-COV-2 infection. A systematic review. (3rd August 2021) - Artemiadis, Artemios; Liampas, Andreas; Hadjigeorgiou, Loizos; Zis, Panagiotis
ABSTRACT: Background׃ COVID-19 (CoranaVirus disease 2019) is an ongoing infectious disease caused by the RNA SARS-CoV-2 virus (Severe Acute Respiratory Syndrome CoronaVirus-2). More than one-third of COVID-19 patients report neurological symptoms and cases of neurological diseases are increasingly accumulating. The aim of this systematic review was to characterize all – to date – reported cases with COVID-19 related myelopathy. Methods׃ Eighteen papers were included in this review. Patients of all ages could be affected, although there is a predilection for middle-aged people. Results׃ There were no significant co-morbidities or immunodeficiencies in the affected patients. COVID-19 related myelopathy started roughly within the first month after COVID-19 onset, either concomitantly with COVID-19 symptoms or within 10 days after their remission. The vast majority of cases fulfilled our criteria for postinfectious transverse myelitis. However, some cases were considered to have had parainfectious or infectious myelitis or, in one case, vascular myelopathy. Motor, sensory and bowel and/or bladder symptoms predominated the clinical presentation of myelopathies, explained mainly by centrally localized and longitudinally extensive lesions within the cervical and/or thoracic segments of the spinal cord. Occasionally lesions were complicated by necrosis and hemorrhages. Treatment with corticosteroids, intravenous immunoglobulin or plasma exchange was offered mostly a mild to marked improvement within a period of some weeks. Conclusions׃ Considering the imminent arrival of new vaccines against COVID-19 pandemic, and their potential risk for postvaccination transverse myelitis, this characterization of COVID-19 related myelopathy is of utmost importance.